Structural and functional validation of S-adenosylmethionine decarboxylase as a novel drug target in the malaria parasite, Plasmodium falciparum - Birkholtz, Lyn-Marie (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.